Pembelajaran Inquiry-Based Learning Berbasis Budaya Pesantren Pada Pelajaran Sejarah Kebudayaan Islam Di MTs Pon-Pes Tahfidz Darul Qur’an - Mhd Radli Ginting (Yayasan Salam Cerdas Al-Fattah, 2025)
Learning Islamic Cultural History (SKI) within the pesantren environment requires an approach that not only emphasizes cognitive aspects but also integrates the cultural values that characterize the institution. However, SKI learning at Darul Qur’an Tahfidz Islamic Boarding School Junior Secondary (MTs) still faces challenges, particularly low student engagement and the dominance of lecture-based methods that do not sufficiently encourage critical thinking. This study aims to implement and analyze the effectiveness of Inquiry Learning based on Islamic Boarding School cultural values in improving the quality of SKI instruction. The research employed a qualitative approach using classroom action research (CAR) conducted in two cycles. The theoretical framework draws on the concept of Inquiry Learning integrated with Islamic Boarding School values such as exemplary behavior, independence, deliberation, and learning etiquette. The findings indicate that implementing Inquiry Learning grounded in Islamic Boarding School culture enhances students’ active participation, critical thinking skills, and conceptual understanding of SKI material. Furthermore, improvements were observed in the quality of the learning process, as reflected in more dynamic classroom interactions and stronger relevance between the material and students’ daily lives as santri. The study concludes that inquiry-based learning incorporating Islamic Boarding School cultural values is an effective alternative for improving SKI learning at Darul Qur’an Tahfidz Islamic Boarding School Junior Secondary (MTs).